Can Patience Account For Subnational Differences in Student Achievement? Regional Analysis with Facebook Interests - Eric A. Hanushek; Lavinia Kinne; Pietro Sancassani; Ludger Woessmann (Institute of Labor Economics (IZA), 2023)
Decisions to invest in human capital depend on people's time preferences. We show that differences in patience are closely related to substantial subnational differences in educational achievement, leading to new perspectives on longstanding within-country disparities. We use social-media data - Facebook interests - to construct novel regional measures of patience within Italy and the United States. Patience is strongly positively associated with student achievement in both countries, accounting for two-thirds of the achievement variation across Italian regions and one-third across U.S. states. Results also hold for six other countries with more limited regional achievement data.
Keywords: I21; Z10; 330; patience; student achievement; regions; social media; Facebook